Analisis Ketepatan Guru dalam Menjelaskan Etika dan Politik Pendidikan di SD Islam Cendekia Assalam - Hilyatun Nafi'ah; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study examines the accuracy of teachers in explaining the scope of educational ethics and educational politics at SD Islam Cendekia Assalam. The study addresses the issue that students often understand ethical values and school regulations at a practical level but lack conceptual understanding. The objective is to analyze how accurately teachers deliver these concepts and how it affects students’ comprehension. This research employs a qualitative approach with a field research design. Data were collected through classroom observations, interviews with teachers, and documentation of teaching materials and learning activities. The findings reveal that teachers effectively instill ethical values such as discipline, honesty, responsibility, and respect through habituation and concrete examples. However, the explanation of educational politics remains implicit and is not systematically conveyed as a conceptual framework. As a result, students demonstrate appropriate behavior in daily school life but show limited ability to explain the underlying concepts. The study highlights the need for more structured and concept-oriented teaching strategies to enhance students’ critical understanding of ethics and educational policies.